History of the Lincoln County War - Fulton, Maurice G. (Maurice Garland), 1877-1955 (University of Arizona Press, 1968)
In the annals of western history, the Lincoln County War stands out as a complex and tragic event in which lives were lost, fortunes destroyed, and peaceful citizens transformed into lonely, exiled outlaws. A classic reference work on the era of Billy the Kid, this fast-moving account brings new meaning to the war and to those individuals who became its victims.